Evaluation of User Interface (UI) and User Experience (UX) in A Web-Based Entrepreneurial Student Application - Ellya Kurniawan, Jimmy; Rahmawati, Kuncoro Dewi; Larasati Rembulan, Cicilia; Tanuwijaya, Evan (Jurnal Entrepreneur dan Entrepreneurship, 2026)
Measurement of entrepreneurial orientation remains limited and is predominantly conducted using manual methods. To address this gap, this study aims to develop a web-based application for measuring entrepreneurial orientation—which has not previously been developed—and to examine its reliability, user interface (UI), and user experience (UX). The instrument used is an adaptation of the entrepreneurial orientation scale, which was converted into a website-based format and complemented with recommendation features and user constraint identification. Data were collected through a focus group discussion (FGD) involving junior and senior high school teachers and students (N = 5), as well as a survey of junior and senior high school students (N = 60) following a trial of the web-based "Entrepreneurial Student" application. The results indicate that this web-based instrument demonstrates high reliability, with Cronbach’s alpha ranging from 0.806 to 0.845, and adequate validity, with Corrected Item–Total Correlation (CITC) values ranging from 0.404 to 0.630. After revisions based on user feedback, UI scores were in the "Very Good" category (range 495–554), and UX scores were also in the "Very Good" category (range 258–274). The Entrepreneurial Student application demonstrates promising potential for measuring entrepreneurial orientation among secondary school students. With further testing involving larger samples, the application may be implemented more broadly within the adolescent population.